Improved brain growth and microstructural development in breast milk–fed very low birth weight premature infants - Ottolini, Katherine M. (Acta Paediatr, 2020)
AIM: Breast milk feeding is linked to improved neurodevelopmental outcomes in very low birth weight (VLBW) infants, though the mechanisms are not well understood. This study utilised quantitative magnetic resonance imaging (qMRI) techniques to compare brain growth and white matter development in preterm infants receiving primarily breast milk versus formula feeds. METHODS: We prospectively enrolled infants born at very low birth weight (<1500 g) and <32 weeks gestational age and performed MRI at term-equivalent age. We utilised volumetric segmentation to calculate regional and total brain volumes and diffusion tensor imaging to evaluate white matter microstructural organisation. Daily nutritional data were extracted from the medical record. RESULTS: Nutritional and MRI data were obtained for 68 infants admitted within the first week of life (44 breast milk and 24 formula). Breast milk–fed infants demonstrated significantly larger total brain volumes (P = .04) as well as volumes in the amygdala-hippocampus and cerebellum (P < .01) compared with formula-fed. Infants receiving breast milk also demonstrated greater white matter microstructural organisation in the corpus callosum, posterior limb of internal capsule and cerebellum (P < .01 to .03). CONCLUSIONS: VLBW infants receiving primarily breast milk versus preterm formula in this small exploratory study demonstrated significantly greater regional brain volumes and white matter microstructural organisation by term-equivalent age.